International Trade and Economic Growth an Indian Experience: The Role of External Sector and Government Control in India's Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Role Of The External Sector In The Development Strategy Has Undergone A Radical Change As The Indian Economy Evolved From One That Turned Inward In Pursuit Of Self Reliance Into An Emerging Growth Center With Openness As Its Characteristic. Arranged Development In India Has So Far Proceeded On The Basic Philosophy Of The Mahalonobis Two-Sector Model That Under-Pinned The Second Plan, Although Further Refinements Have Been Added In Successive Models Developed For The Fourth And Fifth Plans. The Mahalonobis Model Stresses The Importance Of Building Up An Entire Structure Of Capital Goods Indigenous, With A View Of Maximizing The Long Run Growth Of Income. Government Control On Economic Activity, Especially Protection From Foreign Competition, Is Necessary For Seeing The Country Through This Period Because Free Competition Would Allocate Resources According To Existing Levels Of Demand, Which Cannot Be Totally Planned In A Mixed Economy.